RISK FACTOR ANALYSIS OF HYPERTENSION DISEASE IN THE ELDERLY AT GIRIREJO STASI IN SAMARINDA - Pertiwi, Gracia Herni; Sastrini, Yovita (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2022)
The aims of the study were to determine: (1) the relationship between family history and the incidence of hypertension (2) the relationship between physical activity and the incidence of hypertension; (3) the relationship between cholesterol and the incidence of hypertension, and (4) the relationship between body mass index and the incidence of hypertension in the elderly. The research was conducted from March – May 2022 at Girirejo Stasi, Samarinda City. The research design used was analytic survey research or analytical observational (non-experimental) with a cross-sectional approach. The population of this study were all elderly people living in the city of Samarinda. A total sample of 30 elderly people was selected based on inclusion and exclusion criteria. Data was collected using a questionnaire, filling out each question item directly to the respondent, consisting of: age, gender and type of work, activity level, cholesterol level, blood pressure, body mass index, family history of hypertension. The results showed that: (1) There was a relationship between a family history of disease and the incidence of hypertension; (2) There is a relationship between physical activity and the incidence of hypertension in the elderly; (3) there is no relationship between body mass index and the incidence of hypertension, and (4) there is a relationship between cholesterol levels and the incidence of hypertension.